The Next Black Box of Formative Assessment: A Model of the Internal Mechanisms of Feedback Processing - Lui, Angela M.; Andrade, Heidi L. (Frontiers in Education, 2022)
In this theoretical paper, we shift the attention from feedback as something given to feedback as something received. After Black and Wiliam (1998) shined a light into the black box of the classroom and identified formative assessment as a way to raise standards of achievement, a large body of research revealed the influence of feedback on learning. Not all such influences were positive, however, which created a need for closer examinations of the nature of feedback. In addition, recent scholarship on assessment as the co-regulation of learning reveals the importance of understanding how students process and use feedback. We present a model of the internal mechanisms of feedback processing that represents hypothesized ways in which initial motivational states drive how students respond to feedback, as well as the cognitive and affective mechanisms of assessment information processing. We first synthesize a review of existing models and then describe our model in detail, emphasizing the internal mechanisms of feedback processing: initial motivational states, emotions elicited by and interpretations of feedback, and decision-making. The paper concludes with implications for the model’s use as a framework for empirical studies that could contribute to the nascent field of research on classroom assessment as the co-regulation of learning.